Is the Higher Employees’ Resilience, the Higher Their Work Engagement Will Be? - Pramanik, Purwanti Dyah; Dewi, Triana Rosalina; Ingkadijaya, Rahmat (Jurnal Penelitian Pariwisata, 2020)
Hotel is a labor-intensive industry which until now still requires a lot of human resources in its work operations. The nature of hotel is open for 24 hours to serve guests, especially in operational departments. Overall hotel employees tend not to last long at work. Some employees state that their decision to leave, due to incompatibility with the work environment. This study aimed to analyze the impact of resilience on hotel employees’ engagement in Jakarta. The study was conducted with a quantitative descriptive approach. Research respondents were hotel employees in Jakarta area. Data was collected by convenience sampling, by distributing questionnaire which consisted of respondents’ profiles and statement of variable X variable (resilience) and Y variable (work engagement). The data was analyzed by using validity and reliability test, descriptive (frequency and mean), Pearson correlation, coefficient determination and simple linear regression test. The study found that there was a strong relationship between resilience and work engagement. The higher employees’ resilience is the higher employee engagement will be.